ANTI-HYPERLIPIDEMIC ACTIVITIES OF ETHYL ACETATE PARTITIONED EXTRACT OF Daucus carota L. SEED IN TRITON X-100 INDUCED HYPERLIPIDEMIC MICE - TIJJANI, HABIBU; OLATUNDE, AHMED; SUBUDAM, SIMON K.; ISHOLA, AHMED A. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2021)
This study evaluated the anti-hyperlipidemic properties of aqueous (AQF) and ethyl acetate (EAF) partitioned fractions of Daucus carota seed in triton X-100 induced hyperlipidemia in mice. Hyperlipidemia was induced by single intraperitoneal injection of freshly prepared triton X-100 (100 mg/kg body weight) in forty (40) mice, which were randomly distributed into 8 groups of 5 mice each (group B - I) and treated with 0.2 mL distilled water, simvastatin, AQF and EAF. Group A served as non-induced untreated mice, which received 0.2 ml distilled water. AQF and EAF did not significantly (p>0.05) improve the liver-body weight ratio except in EAF at 2 mg/kg body weight. Treatment with AQF and EAF significantly decrease (p<0.05) total cholesterol, triglyceride, low-density lipoproteins, atherogenic, coronary artery, and cardiac indices when compared with hyperlipidemic untreated mice. Furthermore, treatment with the partitioned extracts significantly (p<0.05) improved high-density lipoprotein levels in AQF at dose of 6 mg/kg body weight and EAF at dose of 5 mg/kg body weight when compared with hyperlipidemic untreated mice. The results indicated that AQF and EAF partitioned fractions of D. carota seed possesses significant anti-hyperlipidemic activities in triton X-100 induced hyperlipidemic mice and could be beneficial in preventing cardiovascular diseases associated with hyperlipidemia. Keywords: